Pengaruh Media Sosial bagi Tugas Penggembalaan Imam pada Era Revolusi Industri 4.0 - Avelinus Moat Simon (Studia Philosophica et Theologica, 2019)
In the age of Industrial Revolution 4.0, human life is influenced by various of sophisticated technologies. One of them is social media that increasingly develop, and take some impacts in human life. The fact is there are some priests ignore their pastoral duty and this takes the result that the church is separated. Many of priests don’t live up to their calling as good shepherds. They cannot recognize the church members who entrusted to them by a bishop. This study focus on the influence of social media for a priest’s duty. The research method used in the issue is a qualitative method by using literature approach. I found out that a priest is a shepherd for members of catholic community. A priest ordained by a bishop to continue Christ duty. Social media can become a tool and an equipment for a priest to develop the spiritual life and ministry. The attendance of a priest is the presence Christ as a good shepherd for His sheeps.